Virtual screening, synthesis, and bioactivity evaluation for the discovery of β‐N‐acetyl‐D‐hexosaminidase inhibitors. Issue 9 (26th April 2020) - Dong, Yawen; Hu, Song; Zhao, Xiao; He, Qi; Yang, Qing; Zhang, Li
Abstract: BACKGROUND: Molting is an essential insect developmental process, in which a variety of enzymes are involved. The inhibition of these enzymes effect normal insect growth and development and may even cause death. Of Hex1, one of the β‐ N ‐acetyl‐D‐hexosaminidases, is a key enzyme involved in the molting process of the Asian corn borer ( Ostrinia furnacalis ), and is deemed a potential insecticidal target. RESULTS: Based on the crystal structure of Of Hex1, virtual screening was carried out to obtain a novel class of Of Hex1 inhibitors, of which, 28 compounds were subjected to bioactivity evaluation. The compound 3, N ‐(3‐cyano‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophen‐2‐yl)benzamide, showed good inhibition against Of Hex1 with a K i value of 11.2 μM. Structure optimization and molecular docking were applied for the structure–activity relationship analysis. The results also showed that the cyano group of this compound was essential for the maintenance of its inhibitory activity against Of Hex1. Additionally, the interaction between this compound and Trp490, Glu328, Tyr475 and Trp524 were important for inhibitory activity. CONCLUSION: The advantages of the derivatives of 2‐amino‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐3‐carbonitrile, which have simple chemical structures and are easily synthesized, suggests them to be developed further as potential Of Hex1 inhibitors for pest control. © 2020 Society of Chemical Industry Abstract : The 2‐amino‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐3‐carbonitrile derivatives was identified as inhibitors of β‐ N ‐acetyl‐d ‐hexosaminidase, Of Hex1, from Ostrinia furnacalis . These compounds have potent inhibition against Of Hex1, simple chemical structures and can be easily synthesized.